Analisis Tone Warna Dalam Sinematografi Dalam Menciptakan Efek Bahagia Pada Film Dokumenter “ Permata Di Tengah Danau Toba” Sutradara Andi Hutagalung - Teruna Satria Putra; Dani Manesah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This research investigates the role and impact of the use of color tones in documentary films. Through analysis of a number of leading documentary films, this study aims to understand how choosing color tones can influence the audience's experience and convey messages more effectively. The research results show that color tones can create atmosphere, highlight themes, and influence audience emotions. These findings provide additional insight for ocumentary filmmakers to enhance the power of their visual narratives through intelligent use of color palettes